Elements of banking in Singapore - Cheong, Hua Pak. (Singapore : Institute of Banking & Finance, 1978)
This book gives a comprehensive coverage of the elements of banking. Candidates attempting the stage 1 Examination will find that it covers the entire syllabus of the subject of Elements of Banking
Includes bibliographical references and index.
osc 19/9/17
Loans
Keywords: Banks and banking